Disembodying language: Actionality does not account for verb processing deficits in Parkinson's disease. (February 2022) - Aiello, Edoardo Nicolò; Grosso, Margherita; Di Liberto, Asia; Andriulo, Adele; Buscone, Simona; Caracciolo, Claudia; Ottobrini, Monica; Luzzatti, Claudio
Abstract: Background: Motor structures involvement has been traditionally assumed to account for selective deficits of verb (V) vs. noun (N) processing in Parkinon's disease (PD) patients via action semantic impairment (Embodied Cognition Theory, ECT). Nonetheless, post-semantic accounts, as well as extra-linguistic explanations (task difficulty effects), have not been evenly endorsed. This study aimed at investigating neurocognitive underpinnings of N –V discrepanies in PD patients. Methods: PD patients with (PD+) and without (PD-) cognitive impairments were compared to healthy participants (HPs) on tasks evaluating N and V semantic as well as post-semantic processing. Effects of motor content (actionality) of Ns and Vs and of verb argument structure (VAS) complexity were assessed . Results: All groups performed worse in V than in N lexical retrieval. PD patients performed worse than HPs on both lexical and semantic tasks. By contrast, only N/V naming tasks discriminated PD-from PD + patients. PD + patients showed selective difficulties in retrieving low-actionality as well as transitive and unaccusative Vs. No associations were detected between the action semantic measure and V-naming performances. Discussion: ECT-framed explanations cannot account for N –V discrepancies in PD patients. Indeed, these patients showed semantic deficits not limited to the action domain and retrieved most easily high-actionality Vs. N –V discrepancies in PD patients would thus reflect a magnification of a differential processing demand for Vs vs . Ns - which is intrinsic to the neurocognitive system. Nonetheless, PD patients being sensitive to VAS complexity might imply fronto-striatal involvement in V post-semantic processing, possibly at the lemma level. Highlights: Both healthy participants (HPs) and Parkinson's disease (PD) patients show noun-verb ( N –V) discrepancies. action semantic impairment does not account for V deficits in PD patients. N –V discrepancies are likely to reflect task-difficulty effects in both HPs and PD patients: PD patients show argument structure complexity effects in V processing.